2012
DOI: 10.4018/jsds.2012100101
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Supply Chain Network Design with Recovery of Glass Containers

Abstract: Reverse logistics (RL) and closed-loop supply chains (CLSC) have recently received enormous attention due to growing environmental concerns and legislations coupled with the lucrative business potential. The main purpose of this paper is to develop a closed-loop supply chain network design model capable of recovering glass containers. A multi-period multi-product mixed-integer linear programming model is proposed to maximize profit. The strategic design of the supply chain is dealt simultaneously with the tact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The main gap observed in Brazilian companies relates to the lack of studies to assess, amongst other factors, the economic and environmental benefits of reverse logistics (HERNANDEZ et al, 2012). These benefits are corroborated by other research which points to: a reduction of inventory costs by reusing beer bottles (KO et al, 2012); a reduction in the costs of purchasing raw materials through the recycling and re-manufacturing of broken glass packaging (GOLARA et al, 2012); and, finally, a reduction of 31.7% in logistics costs through cutting down the percentage of unusable tyres and increasing the use of rice husks in the manufacture of rubber, reducing the use of oil derivatives by 10,000 tonnes per year (SELLITO et al, 2013).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The main gap observed in Brazilian companies relates to the lack of studies to assess, amongst other factors, the economic and environmental benefits of reverse logistics (HERNANDEZ et al, 2012). These benefits are corroborated by other research which points to: a reduction of inventory costs by reusing beer bottles (KO et al, 2012); a reduction in the costs of purchasing raw materials through the recycling and re-manufacturing of broken glass packaging (GOLARA et al, 2012); and, finally, a reduction of 31.7% in logistics costs through cutting down the percentage of unusable tyres and increasing the use of rice husks in the manufacture of rubber, reducing the use of oil derivatives by 10,000 tonnes per year (SELLITO et al, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…Glass recycling mitigates the extraction of materials from the environment and their final disposal in landfill sites (BLENGINI et al, 2012), resulting in lower costs and environmental gains. Glass residues are used as fill material (GOLARA et al, 2012) and can be reused as glass packaging (KO et al, 2012). Other studies show that glass residues can be used together with polymers for creating new products, improving their mechanical properties (OSMANI, 2012).…”
Section: Figure 1-closed Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…General summaries and basic RL concepts in research logistic include Daugherty et al (2005), De Brito and Dekker (2004). Research on quantitative approaches in RL systems can be found in Ravi and Shankar (2005), Schultmann et al (2006), Tonanont (2009, Golara et al (2012). Particular topics such as distribution, warehousing, and transportation were addressed in Pokharel and Mutha (2009), Korchi and Millet (2011), Asif (2011), Chouinard et al (2005, Geethan et al (2011), Lambert et al (2011), Jayant et al (2011), Schultmann et al (2006, Cespón et al (2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guchhait, Giri, Maiti, and Maiti (2012) presented a genetic algorithm with chromosome's life-time dependent varying population size was used to solve an inventory control problem under two-level trade-credit policy with fuzzy inventory costs in which suppliers provides not only a credit-period for setting account but also a cash discount to retailers. Golara, Mousavi, Tarokh, and Hosseinzadeh (2012) provided a multi-period multi-product mixed integer linear programming model in a closedloop supply chain network design problem. To demonstrate the efficiency and practicability of the model, they also applied that to a real world case of beverage supply chain where the glass containers are either re-used or recycled into their original form.…”
Section: Literature Reviewmentioning
confidence: 99%